THERMAL STABILIZATION OF HORSERADISH PEROXIDASE BY COVALENT CONJUGATION WITH DEXTRAN - Altikatoglu, Melda; Basaran, Yeliz; Arioz, Candan; Kuzu, Huriye (YILDIZ TECHNICAL UNIV, 2009)
In this study, Horseradish Peroxidase-Dextran covalent conjugates were synthesized whose resistance was increased against high temperature. Firstly HRP was purified by affinity chromatography using immobilized Con A. Enzyme-dextran conjugates with different molar ratios were synthesized using dextran aldehyde derivatives (Dextrans 17.500, 75.000, 188.000 Da) and purified enzyme. Activities of synthesized conjugates and purified enzyme at pH 7 is determined after keeping them for 0, 15 and 30 minutes in a 25, 30, 35, 40, 50, 60,70, 80 degrees C temperatured waterbaths and results are compared. In all keeping periods, a slight decline in the activities of HRP-Dextran conjugates against increasing temperatures is observed when it is compared to purified enzyme. Especially the conjugate with 1/10 molar ratio displayed quite well stability against high temperatures.
Keywords: HRP; dextran aldehyde; conjugate; activity; thermal stability; Engineering